Anti-Arrhythmic Effects of Sodium-Glucose Co-Transporter 2 Inhibitors - Jing, Yuling; Yang, Ruixue; Chen, Wen; Ye, Qiang (Frontiers in Pharmacology, 2022)
Arrhythmias are clinically prevalent with a high mortality rate. They impose a huge economic burden, thereby substantially affecting the quality of life. Sodium-glucose co-transporter 2 inhibitor (SGLT2i) is a new type of hypoglycemic drug, which can regulate blood glucose level safely and effectively. Additionally, it reduces the occurrence and progression of heart failure and cardiovascular events significantly. Recently, studies have found that SGLT2i can alleviate the occurrence and progression of cardiac arrhythmias; however, the exact mechanism remains unclear. In this review, we aimed to discuss and summarize new literature on different modes in which SGLT2i ameliorates the occurrence and development of cardiac arrhythmias.